간이검사 및 현장검사의 국내 사용 실태와 품질관리 현황에 대한 조사 - 유수진; 최리화; 박형두; 전사일; 엄태현; Soo Jin Yoo; Rihwa Choi; Hyung-Doo Park; Sail Chun; Tae Hyun Um (Laboratory Medicine Online, 14(4), 2024)
Background: Point-of-care Testing (POCT) offers convenience and rapid results, leading to its increased use as the range of analytes, reagents, and equipment expands. However, limited research has been conducted on the quality-related issues and management practices of POCT in Korea. This study aimed to examine the utilization patterns, quality-related issues, and management systems for POCT in Korean hospitals. Methods: An Excel-formatted questionnaire was emailed to 334 clinical pathologists responsible for POCT at institutions participating in the Laboratory Accreditation Program of the Laboratory Medicine Foundation in 2023. The survey collected data on POCT or handy test reagents used at each institution, including details on analytes, method of measurement, the testing location, the management of the POCT committee, and any quality-related issues. Results: Responses were received for 942 items from 75 institutions (22.5% response rate, with an average of 12.4 items per institution) in March and April 2024. More items were tested in central laboratories (61.7%) compared to clinical departments (30.0%) or both settings (8.3%). Quality-related issues were reported in 36.9% of cases, with over 90% resolved. The frequency of quality-related issues was higher in POCT than in laboratory tests, particularly for items managed by a POCT committee (50.2%) versus unmanaged items (33.3%). The most frequently reported problems were related to internal quality control (23.1%) and external quality control (19.5%) processes. Conclusions: Quality-related issues occurred in over one-third of POCT cases. Effective management by a POCT committee and appropriate internal and external quality control are essential for identifying and resolving these issues. 배경: 편의성과 신속성의 장점을 가진 간이·현장검사는 수행 가능한 항목과 시약 및 소형 장비의 보급이 확대되며 사용이 증가하고 있다. 그러나, 지금까지 국내에서 간이·현장검사의 품질 관련 문제와 관리 현황에 대한 조사가 이루어진 적은 없기에 이번 연구에서는 병원급 의료기관에서의 간이·현장검사 사용형태, 문제발생 현황, 관리체계 등을 조사하고자 하였다. 방법: 2023년 진단검사의학재단 우수검사실 신임인증평가사업에 참여한 334기관의 책임전문의에게 엑셀 형태의 설문지를 전자메일로 발송하였다. 설문 내용에 소속 기관에서 사용하는 모든 간이·현장검사의 시약 전체 목록과 각각의 분석물질, 측정법, 검사 수행부서, 진료부서 검사 항목에 대한 현장검사위원회 관리 여부, 품질 관련 문제의 발생 여부와 그 원인 및 해결 대책을 포함하였다. 결과: 2024년 3-4월 중 6주 동안 75기관(75/334, 22.5%)에서 942건의 자료가 취합되었다(기관당 평균 12.4건). 진단검사의학과 검사실에서만 간이·현장검사를 수행하는 경우(61.7%)가 타 진료부서에서만 수행되거나(30.0%) 검사실과 타 진료부서에서 모두 운영하는 경우(8.3%)보다 많았다. 타 진료부서에서 수행하는 검사 항목의 83.1% (300/361)는 현장검사위원회에서 관리하고 있었다. 무응답 36건을 제외한 응답 906건 중 334건(36.9%)에서 품질 관련 문제가 발생한 적이 있다고 회신하였고, 이 중 90% 이상은 해결되었다. 간이·현장검사 중 품질 관련 문제 빈도는 현장검사위원회에서 관리하는 항목이 관리하지 않는 항목에 비해 높았다(50.2% vs. 33.3%). 품질 관련 문제발생 과정은 내부정도관리(23.1%)와 외부정도관리(19.5%)가 가장 높은 빈도를 보였다. 결론: 간이·현장검사의 1/3 이상에서 품질 관련 문제가 발생하였고, 현장검사위원회의 관리와 내·외부정도관리가 품질 관련 문제를 발견하고 해결하는데 도움이 된다.